Analysis of electro-mechanical relationship in human iPS cell-derived cardiomyocytes sheets under proarrhythmic condition assessed by simultaneous field potential and motion vector recordings - Atsushi Sugiyama; Mihoko Hagiwara-Nagasawa; Ryuichi Kambayashi; Ai Goto; Koki Chiba; Atsuhiko T. Naito; Yasunari Kanda; Akio Matsumoto; Hiroko Izumi-Nakaseko (Elsevier, 2019)
We investigated the electro-mechanical relationship of human iPS cell-derived cardiomyocyte sheets under arrhythmic condition, which was induced by digitalis intoxication along with the electrical train stimulation (n = 4). We adopted motion vector analysis by high-speed video microscopy and extracellular field potential recording by 64-microelectrode array system. The motion vector analysis uncovered local contractile events at resting phase, at which the field potential analysis showed no deflection in any cell sheet. Thus, motion vector analysis may provide supplemental information over field potential recording in detecting Ca2+-triggered arrhythmias, which may become a new strategy for assessing arrhythmic liability of test articles. Keywords: Electro-mechanical relationship, Human iPS cell-derived cardiomyocytes, Motion vector